How to lead OH & S risk management [ a guide for managers and supervisors (Nicholas & Smith, 2007)
Lyn is an experienced manager and facilitator. She is showing a group of managers from manafacturing and service companies how to facilitate the risk mangement process in OH & S. They work with real case studies from merck sharp and dohme an international pharmaceutical manufacturer and AMP a major financial services provider. Lyn covers the four steps of risk mangement and demonstrates the key facilitation skills that managers need. Together, the steps and skills maximise the contribution from employees and therefore make the risk mangement process effective